Radar monitoring of seasonal bird migration over Central Israel - Leonid Abramovich Dinevich; Yossi Leshem (Наука. Инновации. Технологии)
A radar ornithological station has been created based on the meteorological radar MRL-5 and a specially designed algorithm. The system enables to plot radar charts within the radius of 60 km combining meteorological data with vectors of bird field flying at different heights and pass these charts online over to air traffic control operators. The data accumulated in the study made it possible to obtain certain characteristics of seasonal bird migration over Central Israel. The system and the results of the study have become an integral part of ensuring air safety for Israeli military aircraft.